Menstrual Hygiene Practices and Knowledge Among High School Girls of Rural Kolar - Krishnamurthy, Latha; Ranganath BG; Shruthi M N; Venkatesha, Mahesh (National Journal of Community Medicine, 2016)
Introduction: Poor Menstrual hygiene among women of developing countries is an insufficiently acknowledged problem. Objectives were to know practices among school girls, their knowledge and facilities available at school. Methodology: A cross sectional study was conducted in July 2011 to October 2011 at Govt High school, Bangarpet, Kolar. 171 Girls participated in the study. A structured questionnaire was applied to obtain information on Menstrual hygiene and practices. Focussed group discussion(FGD) was also conducted. Health education on information regarding menstrual hygiene was provided after the study. Results: Mean age was 14.2 years among these girls 88 of them had attend menarche. 48.8 % of them used both sanitary pads and cloth as menstrual absorbent, 63.6% did not have knowledge about menstruation before attaining menarche, 72.7 %, 2.2%, had restrictions for religious occasions, for going to school respectively during menstruation. 24.24% did not change absorbent during school hours. 45.45% changed in bathroom, 30.3% went home. Conclusion: Hygiene practices and knowledge were inadequate. It can be improved if adequate facilities are provided for girls at school. Information on reproductive health needs to be provided to girls before attaining menarche.